Neck cooling provides ergogenic benefits after heat acclimation during exercise in the heat - Zhang, G.; Xin, G.; Li, H.; Ma, P.; Wang, H. (Frontiers in Physiology, 2025)
Background: Both heat acclimation and neck cooling have been shown to alleviate heat stress and may help maintain exercise performance in the heat. However, no previous research has been determined their combined effects on thermal perception and physiological responses during exercise in the heat.